2007
DOI: 10.1021/pr0604458
|View full text |Cite
|
Sign up to set email alerts
|

N-linked Glycosylation Profiling of Pancreatic Cancer Serum Using Capillary Liquid Phase Separation Coupled with Mass Spectrometric Analysis

Abstract: Glycoproteins play important roles in various biological processes including intracellular transport, cell recognition, and cell-cell interactions. The change of the cellular glycosylation profile may have profound effects on cellular homeostasis and malignancy. Therefore, we have developed a sensitive screening approach for the comprehensive analysis of N-glycans and glycosylation sites on human serum proteins. Using this approach, N-linked glycopeptides were extracted by double lectin affinity chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
145
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 45 publications
5
145
0
Order By: Relevance
“…[21][22][23][24][25][26][27][28][29][30][31][32][33] However, less attention has been paid to the study of glycosylation during and after treatment. [34][35][36] In this regard, our present work is aimed to MS investigation of N-glycans in human breast MCF-7 carcinoma and T-lymphoblastoid CEM cells vs oligosaccharide profiles obtained from cells treated by ex-vivo assay with Herceptin alone or combined with Lipofectamine (LipA) and plasmid DNA.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30][31][32][33] However, less attention has been paid to the study of glycosylation during and after treatment. [34][35][36] In this regard, our present work is aimed to MS investigation of N-glycans in human breast MCF-7 carcinoma and T-lymphoblastoid CEM cells vs oligosaccharide profiles obtained from cells treated by ex-vivo assay with Herceptin alone or combined with Lipofectamine (LipA) and plasmid DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Serum of patients with cirrhosis showed a heterogeneous distribution of N-glycans compared with healthy samples [23]. In a study on human pancreatic cancer, serum samples contained N-glycans with increased fucosylation and sialylation relative to those from healthy individuals [24]. Samples in the study of ovarian cancer patients also showed a number of neutral oligosaccharides that appeared related to cancer [25].…”
mentioning
confidence: 99%
“…When a mixture of glycopeptides is analyzed, one current roadblock is being able to determine why the particular glycopeptide ion has changed in abundance, i.e., is it due to changes in glycosylation on a given protein or due to changes in the protein's concentration, relative to the other species being analyzed [4]? Our method, which characterizes the entire glycosylation profile for a given glycoprotein as part of the quantitation process, is ideally suited to solving this problem.…”
Section: Mixture Analysismentioning
confidence: 99%
“…This introduces many problems in biomarker discovery, such as not being able to identify whether or not the glycan's concentration increased because a protein containing that glycan was overexpressed, or if one or several proteins' glycosylation profile changed, causing the glycan to be more abundant, even though the protein level(s) are not altered [4]. In contrast to glycan analysis, glycopeptide analysis provides glycosylation site-specific information for purified proteins [17,20,21], and it could potentially be useful in distinguishing between glycosylation changes and protein expression changes, since the protein information is encoded in the glycopeptide.…”
mentioning
confidence: 99%
See 1 more Smart Citation